Protecting liver sinusoidal endothelial cells suppresses apoptosis in acute liver damage. Issue 7 (12th November 2015) - Tanoi, Tomohito; Tamura, Takafumi; Sano, Naoki; Nakayama, Ken; Fukunaga, Kiyoshi; Zheng, Yun‐Wen; Akhter, Afsana; Sakurai, Yu; Hayashi, Yasuhiro; Harashima, Hideyoshi; Ohkohchi, Nobuhiro
Abstract : Aim: Apoptosis is associated with various types of hepatic disorders. We have developed a novel cell‐transfer drug delivery system (DDS) using a multifunctional envelope‐type nano device that targets liver sinusoidal endothelial cells (LSECs). The purpose of this study was to determine the efficacy of the novel DDS containing siRNA at suppressing apoptosis in LSECs. Methods: Bax siRNA was transfected into a sinusoidal endothelial cell line (M1) to suppress apoptosis induced by an anti‐Fas antibody and staurosporine. C57BL/6J mice were divided into three groups: (i) a control group, only intravenous saline; (ii) a nonselective group, injections of siRNA sealed in the nonselective DDS; and (iii) an LSEC‐transfer efficient group, injections of siRNA sealed in an LSEC‐transfer efficient DDS. Hepatic cell apoptosis was induced by an anti‐Fas antibody. Results: Bax siRNA had an anti‐apoptotic effect on M1 cells. Serum alanine aminotransferase was reduced in the LSEC‐transfer efficient group, as were cleaved caspase‐3 and the number of terminal deoxynucleotidyl transferase dUTP nick end labeling positive hepatocytes. Silver impregnation staining indicated that the sinusoidal space was maintained in the LSEC‐transfer efficient group but not in the other groups. Electron microscopy showed that the LSECs were slightly impaired, although the sinusoidal structure was maintained in the LSEC‐transfer efficient group. Conclusion: Hepatocyte apoptosis was reduced by the efficient suppression of LSEC apoptosis with a novel DDS. Protecting the sinusoidal structure by suppressing LSEC damage will be an effective treatment for acute liver failure.